The "far-west" of Anopheles gambiae molecular forms - Caputo, Beniamino (2011)
The main Afrotropical malaria vector, Anopheles gambiae sensu stricto, is undergoing a process of sympatric ecological diversification leading to at least two incipient species (the M and S molecular forms) showing heterogeneous levels of divergence across the genome. The physically unlinked centromeric regions on all three chromosomes of these closely related taxa contain fixed nucleotide differences which have been found in nearly complete linkage disequilibrium in geographic areas of no or low M-S hybridization. Assays diagnostic for SNP and structural differences between M and S forms in the three centromeric regions were applied in samples from the western extreme of their range of sympatry, the only area where high frequencies of putative M/S hybrids have been reported. The results reveal a level of admixture not observed in the rest of the range. In particular, we found: i) heterozygous genotypes at each marker, although at frequencies lower than expected under panmixia; ii) virtually all possible genotypic combinations between markers on different chromosomes, although genetic association was nevertheless detected; iii) discordant M and S genotypes at two X-linked markers near the centromere, suggestive of introgression and inter-locus recombination. These results could be indicative either of a secondary contact zone between M and S, or of the maintenance of ancestral polymorphisms. This issue and the perspectives opened by these results in the study of the M and S incipient speciation process are discussed.